Cover Image Volume 28, Issue 8. (12th July 2018) - Jakobsen, J. R.; Jakobsen, N. R.; Mackey, A. L.; Koch, M.; Kjaer, M.; Krogsgaard, M. R.
Abstract : The cover image, by J. R. Jakobsen et al., is based on the Original Article Remodeling of muscle fibers approaching the human myotendinous junction, DOI:10.1111/sms.13196 .